1984
DOI: 10.1136/thx.39.7.535
|View full text |Cite
|
Sign up to set email alerts
|

Predicted normal values for maximal respiratory pressures in caucasian adults and children.

Abstract: ABsTRAcr Maximal respiratory pressures at the mouth (PEm. and PI,M.) have been measured in 370 normal caucasian children and adults. Age, height, and weight were recorded for all subjects and incorporated in a stepwise multiple regression analysis to determine prediction equations for the maximal respiratory pressures in the children and adults for both sexes. In men Pi,. and PEmax were significantly correlated only with age (p < 0-001 and < 0-035 respectively), whereas in women they were correlated with heigh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

38
436
11
53

Year Published

1997
1997
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 602 publications
(549 citation statements)
references
References 7 publications
38
436
11
53
Order By: Relevance
“…We found that mean maximal inspiratory and expiratory static pressures were low in A-T adolescents when compared to published normal predicted values in children. 21 In our population the low maximal inspiratory and expiratory pressures may reflect decreased muscle mass. Prior studies in healthy individuals have shown that adolescent males generally have higher PI max and PE max values compared to females 21,22 and that this difference was secondary to greater muscle mass following puberty.…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…We found that mean maximal inspiratory and expiratory static pressures were low in A-T adolescents when compared to published normal predicted values in children. 21 In our population the low maximal inspiratory and expiratory pressures may reflect decreased muscle mass. Prior studies in healthy individuals have shown that adolescent males generally have higher PI max and PE max values compared to females 21,22 and that this difference was secondary to greater muscle mass following puberty.…”
Section: Discussionmentioning
confidence: 73%
“…21 In our population the low maximal inspiratory and expiratory pressures may reflect decreased muscle mass. Prior studies in healthy individuals have shown that adolescent males generally have higher PI max and PE max values compared to females 21,22 and that this difference was secondary to greater muscle mass following puberty. 22 Although our sample size was small we found no difference in PI max or PE max values between genders.…”
Section: Discussionmentioning
confidence: 73%
“…Their baseline mean age was 9.4 years and mean 6MWT distance at baseline was 363.2m (Table 4). Mean pulmonary function tests (MIP, MEP, and FVC percentage of predicted) at baseline were within normal ranges34 (see Table 2). …”
Section: Resultsmentioning
confidence: 80%
“…Up to 5 efforts were allowed, and the best effort results were used for analysis. Results were converted to percentage of predicted values employing the widely used methodologies of Wilson et al34 for MIP and MEP and Polgar and Varuni35 for FVC.…”
Section: Methodsmentioning
confidence: 99%
“…Of these 33 articles, only eight describe the type of mouth piece, 11 describe the presence and size of a pressure relief port, varying from 0.5 to 1.8 mm, and 11 report the minimum time of respiratory effort. Eight of 33 applied predictive equations to the analysis, five used Black and Hyatt, 17 two Wilson et al, 18 and one Rochester,19 with the rest considering only the absolute values.…”
Section: Discussionmentioning
confidence: 99%